2016
DOI: 10.1021/acsami.6b02099
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of Au-Island-Covered Pd Nanotubes with Abundant Heterojunction Interfaces for Enhanced Electrooxidation of Alcohol

Abstract: Here, we, for the first time, synthesized Pd nanotubes covered by high-density Au-islands, in which abundant exposed Pd−Au heterojunction interfaces are present and the content of element Au can be easily controlled. The optimized nanostructures show remarkably enhanced activity for catalyzing different alcohols in alkaline media than commercial Pd/C. The mass activity is 9.66, 1.83, and 4.60 A mg metal −1 toward the electrooxidation of ethanol, glycerol, and ethylene glycol in alkaline media, which is about 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 32 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…An open tube with a large diameter is highly beneficial for ion accessibility and diffusion. Various wet chemical methods have been attempted for palladium nanotube synthesis . Nevertheless, most of these nanotube products were collected as piled‐up powders.…”
Section: Introductionmentioning
confidence: 99%
“…An open tube with a large diameter is highly beneficial for ion accessibility and diffusion. Various wet chemical methods have been attempted for palladium nanotube synthesis . Nevertheless, most of these nanotube products were collected as piled‐up powders.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al 40 making a metal content ratio of 1:1, and comparing to other groups; the catalyst exhibited S C H E M E 3 Linear sweep curves of Pt (left) and Pd electrode in alkaline media 31 [Colour figure can be viewed at wileyonlinelibrary.com] unique one-dimension nanowires (1D NWs) structure due to the optimum ratio of dual capping agents, polyvidone (PVP), and C 19 H 42 BrN (CTAB). Pd-Au NWs were able to produce high mass activities for a short time, but Pt-Au NWs could retain higher mass activities for a longterm period due to better durability.Lam et al, 41 Ottoni et al, 42 Cai et al, 43 Rezaei et al, 44 Dong et al, 45 and Yahya et al 46,47 researched various molar ratios for Pd/Au catalyst. Lam et al 41 reported Pd-Au bi-functional mechanism caused oxidation removal of residual intermediate poisons on active Pd surface to enable GOR to restart.…”
Section: Development Of Pt-based and Pdbased Catalyst With Gold Metalmentioning
confidence: 99%
“…34 They also found that the Pd/Au equilibrium composition is the most active and can break all the glycerol C C bonds in a single process, leading to carboxylic acid production pathways. Cai et al 43 synthesized through Te nanowires template, where the Pd was in the form of nanotubes 48 covered by controllable precursor, Au (Scheme 4). The structure provided Pd-Au heterogenous junctions formation and enabled the catalyst to selfsupport itself for better catalytic activity than standalone catalysts Pd/C and Pd NTs.…”
Section: Development Of Pt-based and Pdbased Catalyst With Gold Metalmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the use of 1D Pt and Pd nanomaterials, alloyed or decorated with Au, has shown significant catalytic activity owing to their synergistic effects and large surface areas [18,[25][26][27][28][29][30][31]. To this end, ultrathin nanowires (NWs) have become widely used in fuel cells, offering remarkable catalytic performances [32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%